Międzynarodowe otoczenie marketingowe przedsiębiorstwa - Skulski, Przemysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Increased influence on international environment in strategic activity of enterprises has been noticed in last years. In terms of introducing the marketing to foreign markets there interact two things: the increase of speed of changes and their direction, which is hard to predict. Because of this, the exact analysis of environmental elements plays such important role in a process of preparing marketing strategy for entering foreign markets. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 345-357